The Impact of active surveillance culture and decolonization programs on NICU MRSA transmission: A multicenter, mechanistic modeling approach. (4th October 2017) - Pierce, Rebecca; Elward, Alexis; Bryant, Kristina; Lessler, Justin; Milstone, Aaron M
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) remains a major threat to patient safety in the neonatal intensive care unit (NICU). The aim of this study was to assess the effectiveness of active surveillance cultures (ASC) and decolonization in reducing MRSA transmission in the NICU. Methods: Retrospective cohort data, including admission and discharge times, weekly surveillance culture results and mupirocin-administration information, were collected from three urban, tertiary care NICU in the US. The study period was 2007–2014, during which ASC and decolonization strategies were employed for MRSA control. We used Markov-Chain Monte Carlo methods to fit a probabilistic transmission model to the data. To account for the interval-censored nature of weekly surveillance screening, we used an integrated Bayesian framework to impute the date of conversion to MRSA-positive. We estimated the risk of MRSA acquisition associated with non-patient sources, undetected MRSA carriers, detected MRSA carriers on contact precautions, and MRSA carriers on contact precautions that also received decolonization treatment. Results: Of the 12, 677 neonates that were screened for MRSA colonization at study sites, 533 (4.2%) had a MRSA-positive surveillance culture. Neonates with undetected MRSA colonization were estimated to be the source of 67% (95% credible interval [CI]: 0.64–0.69) of MRSA acquisition. Compared with undetected MRSA carriers, detection and placement on contact precautions deceased the odds of transmission by 99.8% (odds ratio [OR]: 0.0016, 95% CI: 0.0000026–0.033), 99.6% (OR = 0.0036, 95% CI: 0.0000025–0.13), and 99.8% (OR = 0.0024; 95% CI: 0.00000042–0.043) at sites A, B, C, respectively. A 99.9% reduction in transmissibility was sustained among MRSA carriers who also received decolonization treatment (OR = 0.0014, 95% CI: 0.0000080–0.024). Conclusion: In this multi-centered NICU cohort, ASC and decolonization programs were highly effective in reducing transmission risk from MRSA carriers. Detection of MRSA carriers and the use of contact precautions, alone, were associated with a near-complete reduction in transmission risk. Improving time-to-detection as well as prioritizing nonpatient reservoirs of MRSA could further reduce MRSA acquisition in the NICU. Disclosures: All authors: No reported disclosures.